Prevalensi Skabies Pada Santri Dan Hewan Reservoir Di Pondok Pesantren Kota Palangka Raya - Afrilia, Adella; Augustina, Indria; Teresa, Astrid; Widiarti, Astri; Ratnasari, Arini; Jabal, Arif Rahman (Fakultas Kedokteran Universitas Palangka Raya, 2025)
Scabies is a skin infection caused by the Sarcoptes scabiei mite. The main symptom experienced during a scabies infestation is nighttime itching (pruritus nocturna), accompanied by skin lesions in the form of burrows (kunikulus) at preferred sites. This study aims to determine the prevalence of scabies among students (santri) and identify potential animal reservoirs in Islamic boarding schools in the city of Palangka Raya. A Quantitative descriptive with cross-sectional design. Sampling was taken using a total sampling technique and skin scraping method and the samples obtained were examined using a microscope with 40x magnification. This research was conducted at the Hidayatul Insan, Darul Amin, Al-Wafa, Manba'u Darissalam, and Nurul Ihsan Islamic boarding schools. The samples in this study were students from 5 Islamic boarding schools totaling 142 students and reservoir animals in Palangka Raya City Islamic Boarding Schools. Data processing and analysis was obtained using the SPSS 26.0 program. The prevalence of scabies among students in 5 Islamic boarding schools in Palangka Raya City was 38.73%. The prevalence of scabies in reservoir animals in 5 Islamic boarding schools in Palangka Raya City is 0%. No stages of Sarcoptes scabiei mites and eggs were found at the Palangka Raya City Islamic Boarding School